2020
DOI: 10.3390/cells9051160
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endoplasmic Reticulum Stress Sensor IRE1α in Cellular Physiology, Calcium, ROS Signaling, and Metaflammation

Abstract: Inositol-requiring transmembrane kinase endoribonuclease-1α (IRE1α) is the most prominent and evolutionarily conserved unfolded protein response (UPR) signal transducer during endoplasmic reticulum functional upset (ER stress). A IRE1α signal pathway arbitrates yin and yang of cellular fate in objectionable conditions. It plays several roles in fundamental cellular physiology as well as in several pathological conditions such as diabetes, obesity, inflammation, cancer, neurodegeneration, and in many other dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 248 publications
(240 reference statements)
3
58
0
Order By: Relevance
“…Studies have shown that IRE1α plays an important role in mediating ROS-generation ( Abuaita et al, 2015 ) and 4μ8C has been described as a potent ROS-scavenger ( Chan et al, 2018 ). IRE1α generates ROS through Ca 2+ -mediated signaling between the IRE1α-InsP3R pathway in the ER and the redox-dependent apoptotic pathway in the mitochondrion, as well as via activation of CHOP, BIP and through XBP1-splicing ( Riaz et al, 2020 ; Zeeshan et al, 2016 ). In line with these findings, we found a significant reduction in intracellular ROS-levels after treatment with 4μ8C in LX2, HepG2 and Huh7-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IRE1α plays an important role in mediating ROS-generation ( Abuaita et al, 2015 ) and 4μ8C has been described as a potent ROS-scavenger ( Chan et al, 2018 ). IRE1α generates ROS through Ca 2+ -mediated signaling between the IRE1α-InsP3R pathway in the ER and the redox-dependent apoptotic pathway in the mitochondrion, as well as via activation of CHOP, BIP and through XBP1-splicing ( Riaz et al, 2020 ; Zeeshan et al, 2016 ). In line with these findings, we found a significant reduction in intracellular ROS-levels after treatment with 4μ8C in LX2, HepG2 and Huh7-cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved not only in neurodegenerative diseases but also in obesity, in ammation and T2DM, among others. Therefore, its inhibition could offer an interesting avenue for AD (91)(92)(93). Going further, ATF3 is a stress-induced and adaptive-responsive gene located downstream of eIF2α which basal levels are low.…”
Section: Discussionmentioning
confidence: 99%
“…IRE1α is a multi-functional protein (Riaz et al, 2020), we wanted to examine the importance of IRE1α in PA induced CIK cell inflammation and autophagy, CIK cells were exposed to PA, with or without 4μ8c. As shown in Fig.…”
Section: Inhibition Of Ire1α Ameliorates Pa Induced Autophagy and Infmentioning
confidence: 99%